Novel Stability Indicating RP-HPLC Method Development and Validation for Simultaneous Estimation of Alfuzosin and Dutasteride in Pharmaceutical Dosage Form - Diyya, Keerthana (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The present study was to develop a simple, accurate and stable reverse phase liquid chromatographic method and validate in bulk drug and pharmaceutical dosage form for the simultaneous determination of Alfuzosin Hydrochloride (ALF) and Dutasteride (DUT). Materials and Methods: Chromatographic separation has been accomplished using an XTerra C18 Column (150×4.6mm, 5μm particle size) as the stationary phase, with an isocratic system of mobile phase Ammonium dihydrogen phosphate buffer (pH 6.5) and methanol (25:75 proportions) at a flow rate of 1.0 mL/min, detection was executed at 246 nm using an UV detector. The optimized method was validated in accordance to International Conference on Harmonization guidelines. Results: The method developed was found to be linear as regression analysis showed good correlation (R2 = 0.999) with a linear curve at concentration range of 25-150 μg/mL for ALF and 1.25-7.5 μg/mL for DUT. The approach was unique as it was free of degradants in spite of subjecting the drugs to forced degradation. The percentage recovery was in the range of 99.55 and 99.23 % for ALF and DUT respectively from the pharmaceutical dosage form. The developed method showed accurate, precise, robust results with an LOD and LOQ of 0.41 and 0.71 μg/mL and 4.27 and 2.14 μg/mL respectively. Conclusion: Due to the flexibility, accuracy and high precision, the developed method can be employed in routine analysis of bulk and dosage forms.
Keywords: Alfuzosin Hydrochloride; Dutasteride; RP-HPLC; Method development; Validation; Degradation